(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: Rice is a prosperous food subsidy in the form of rice earmarked for low-income households as the efforts of the government to improve food security and provide social protection to targeted households. The success of Rice Program prosperity is measured by the level of achievement 6T indicators, namely: the right target, the right amount, the right price, right time, right quality and right administration. The program aims to reduce the burden of Target Households spending through the partial fulfillment of staple food needs in the form of rice and prevent a decrease in consumption of energy and protein. The purpose of this study is to identify the effectiveness of Rice Welfare Program in improving public welfare in the District Ranoyapo Preprosperous South Minahasa regency. Data collection techniques in this research is through: Observation namely direct observation to the study site, conduct interviews and documentation. Results of the evaluation showed that the program in the District Ranoyapo prosperous rice was not effective because there are still some things that are not appropriate as the data receiver has not updated the program, the government is less involved mislead the public so that people do not know clearly the price and the actual amount of rice. Likewise, there is a supplementary budget that is charged to the public for reasons of money transport vehicles rice and supervision of the district governments are still lacking. Keywords: Program Effectiveness Rice Welfare, Welfare Pre prosperous society.